The clinical spectrum of syphilitic balanitis of Follmann: report of five cases and a review of the literature. (16th July 2016) - Mainetti, C.; Scolari, F.; Lautenschlager, S.
Abstract: Background: Eugène Follmann first described syphilitic balanitis as a manifestation of primary syphilis in 1948 and since then it has been known as syphilitic balanitis of Follmann (SBF). So far, SBF has rarely been described in literature. Objectives: We are reporting five additional cases of SBF considering the broad differential diagnosis of balanitis. Methods: A review of the available literature of SBF was performed and five additional cases analyzed. Results: In our case series, the clinical appearance of SBF shows a heterogeneous spectrum varying from painful oedematous balanoposthitis with beginning paraphimosis to superficial erosive balanitis and even to painless induration of the glans. Conclusions: SBF might be seen more frequently than has been described due to misinterpretation. Therefore primary syphilis should be included in the differential diagnosis of balanitis and balanoposthitis.